Odpowiedzi

2010-01-11T22:15:07+01:00
(a+b)-(2a-b)-(a-2b)= a+b-2a+b-a+2b= -2a+4b
(3x-y+1)-(x+y)+(x+y)+(y-x)=3x-y+1-x-y+x+y+y-x=2x+1
-(kx+ny)-(3kx+2ny)+(5kx-3ny)=-kx-ny-3kx-2ny+5kx-3ny=kx-6ny
2010-01-11T22:15:16+01:00
A)a+b-2a+b-a-2b=b-2a
b)(3x-y+1)-(x+y)+(y+x)+(y-x)=3x-y+1-x-y+y+x+y+x=4x+1
c)-(kx+ny)-(3kx+2ny)+(5kx-3ny) = -kx-ny-3kx-2ny-5kx+3ny=-9kx
2010-01-11T22:40:55+01:00
A)
(a+b)-(2a-b)-(a-2b) = a+b-2a+b-a+2b = a-2a-a+b+b+2b = -2a+4b
b)
(3x-y+1)-(x+y)+(y+x)+(y-x) = 3x-y+1-x-y+y+x+y-x = 3x-x+x-x-y-y+y+y+1 = 2x+1
c)
-(kx+ny)-(3kx+2ny)+(5kx-3ny) = -kx-ny-3kx-2ny+5kx-3ny = -kx-3kx+5kx-ny-2ny-3ny = kx-6ny